Factors affecting the earthworm population in contrasting weed management systems in a banana plantation in Mindanao, Philippines - Fusilero, Ma. Abegail T. (2009)
Earthworms are significant in agriculture not only for their role in maintaining soil fertility, but they also serve as indicators of unfavorable effects of agriculture practice. To determine the factors that may affect earthworm populations under contrasting weed management practice in banana plantation, a long-term field experiment was initiated. This was followed up with acute toxicity and pot experiment tests involving paraquat, a herbicide used in the chemical weed management treatment. There was no significant difference in earthworm population counts for the manual and chemical plots in 15% and 25% slopes after one year observation (15% F0.1.88, P=0.40; 25% F0.02, P=0.89). variation in earthworm population could be attributed to differences in soil moisture, pH, organic matter, organic mulch and soil cover. When earthworms were exposed to paraquat concentrations up to 50x that normality used in agriculture in the contact filter paper test, there was no significant difference in their response (F=1.92, P=0.09) the normal rate of paraquat application used in the field was clearly not toxic, but concentrations 10x and higher than normal rate tend to cause a drop of response to stimuli. In the laboratory pot experiment, change in earthworm weights among the varying rates of paraquat was not significant (F=0.27, P=0.94). it is noteworthy that even at very high concentrations (50x normal), the earthworm did not show a significant growth rate reduction. The experiments suggest that chemical weed management does not pose a significant threat to earthworms under the conditions studied
Thesis (BS Biology) -- University of the Philippines Mindanao, 2009
Keywords: Bananas; Bananas -- Plantations; Bananas -- Plantations -- Mindanao -- Philippines; Earthworms; Weed management; Weed management -- Practices; Soil pH; Earthworms -- Population; Weeds -- Control; Manual weeding; Chemical weeding; Earthworms -- Identification; Paraquat -- Toxicity; Rainfall; Soil -- Analyses; Earthworms -- Ecology